Implementation of clinical practices and pathways optimizing ACS patients lipid management: Focus on eight European initiatives. (December 2020) - Alings, Marco; Descamps, Olivier; Guillon, Benoit; Leosdottir, Margret; Maggioni, Aldo P.; Recasens, Lluis; Speidl, Walter S.; Tripodi, Rosario V.; Landmesser, Ulf; Catapano, Alberico L.; Pirillo, Angela
Abstract: Post-acute coronary syndrome (ACS) patients are at very high cardiovascular risk. Despite current guidelines strongly recommend to reduce LDL-C levels and initiation of high-intensity statins as early as possible in patients admitted with an ACS, less than half of ACS patients receive a high intensity statin, and a high percentage of has LDL-C well above the goal despite therapy. There are multiple reasons for that, including physician lack of guideline adherence, patient lack of compliance with treatment, and lack of standardized procedures. Furthermore, although the prevalence of familial hypercholesterolemia is higher among patients with ACS, this condition remains poorly estimated. To fill these gaps, some European countries have launched local initiatives for the in-hospital and post-discharge ACS patient lipid management. It appears that ensuring optimal therapy during hospitalization and dedicated follow-up protocols results in a significant improvement of lipid levels in these very high risk patients, which may translate into a reduced risk of recurrent future events. Graphical abstract: Image 1 Highlights: Post-ACS patients are at very high cardiovascular risk. Lipid management of ACS patients is overall suboptimal. The screening program for the detection of FH is largely not applied. European in- and post-hospital initiatives were undertaken to fill these gaps.